2-Difluoromethylpyridine as a bioisosteric replacement of pyridine-N-oxide: the case of quorum sensing inhibitors. Issue 12 (14th October 2021) - Tung, Truong Thanh; Nguyen Quoc, Thang
Abstract : Herein, we demonstrate that 2-difluoromethylpyridine is a bioisosteric replacement of pyridine- N -oxide. This work could open a new path for bioisosteric replacement in drug discovery and development. Abstract : Herein, we demonstrate that 2-difluoromethylpyridine is a bioisosteric replacement of pyridine- N -oxide. Using the quorum sensing inhibitor 4NPO as a model compound, a library of 2-difluoromethylpyridine derivatives was designed, synthesized, and evaluated toward quorum sensing activity, biofilm formation, anti-violacein activity, and protease activity. As a result, compounds 1 (IC50 of 35 ± 1.12 μM), 5 (IC50 of 19 ± 1.01 μM), and 6 (IC50 of 27 ± 0.67 μM) showed a similar or better activity in comparison to 4NPO (IC50 of 33 ± 1.12 μM) in a quorum sensing system of Pseudomonas aeruginosa . In addition, compounds 1, 5, 6, and 4NPO showed good antibiofilm biomass of Pseudomonas aeruginosa and reduced violacein production in Chromobacterium violaceum . In terms of protease activity, compounds 1, 5, and 6 showed significant activity compared to 4NPO . Overall, the replacement of pyridine- N -oxide by 2-difluoromethylpyridine enhances the activity of the model compound, which could open a new path for bioisosteric replacement in drug discovery and development.